Slide:ology : the art and science of creating great presentations - Duarte, Nancy (Beijing ; Sebastopol, CA : O'Reilly Media, 2008)
"No matter where you are on the organizational ladder, the odds are high that you've delivered a high-stakes presentation to your peers, your boss, your customers, or the general public. Presentation software is one of the few tools that requires professionals to think visually on an almost daily basis. But unlike verbal skills, effective visual expression is not easy, natural, or actively taught in schools or business training programs. slide:ology fills that void." "Written by Nancy Duarte, Principal of Duarte Design, the firm that created the presentation for Al Gore's Oscar-winning film, An Inconvenient Truth, this book is full of practical approaches to visual story development that can be applied by anyone. The book combines conceptual thinking and inspirational design, with insightful case studies from the world's leading brands." "Millions of presentations and billions of slides have been produced - and most of them miss the mark. slide:ology will challenge your traditional approach to creating slides by teaching you how to be a visual thinker. And it will help your career by creating momentum for your cause."--BOOK JACKET.
Creating a new slide ideology -- Creating ideas, not slides -- Creating diagrams -- Displaying data -- Thinking like a designer -- Arranging elements -- Using visual elements: background, color, and text -- Using visual elements: images -- Creating movement -- Governing with templates -- Interacting with slides -- Manifesto: the five theses of the power of a presentation.
Includes bibliographical references (p. 262-263) and index.
Keywords: Business presentations; Visual communication; Presentation graphics software